CSR Decoupling and Tax Avoidance: a Conceptual Framework - Noorsakinah Abdul Wahab; Nurliana Md Rahin; Mohd Zulkhairi Mustapha (Australasian Accounting, Business and Finance Journal, 2022)
This paper proposes a conceptual framework to investigate the relationship between CSR and tax avoidance. CSR and tax avoidance are claimed to share a similar feature of morality, thereby forming the basis of argument in the linkage between the two strategies at corporate level. While prior studies examined the relationship to ascertain corporate intention of engaging in CSR, this paper proposes that the corporate intention, implied by CSR decoupling, be embedded in the framework to investigate corporate perception on what constitutes moral judgment. Specifically, this paper proposes a framework to understand if companies view tax avoidance as an immoral act. The premise of neo-institutional theory is utilised to explain the intention of CSR, through CSR decoupling, and its influence on tax avoidance. This paper proposes that the significant gap in the literature should be addressed by incorporating the intention of CSR into examination rather than concluding it; and seek to ascertain if companies view tax avoidance as immoral, concluding the huge assumption that prior studies have relied on.
Keywords: Business Ethics; Corporate Social Responsibility; CSR Decoupling; Tax Avoidance